Improving Children’s English Vocabulary Mastery Through The TGT Learning Model And Vocabulary Cards - Rais, Halimah Khoirun Ni’mah; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
Learning the language is very important, including learning English. However, based on research conducted by EF World Institute of Education English First announced the first comprehensive report, the on index English proficiency index in 44 English proficiency countries in Indonesia is very low in the 34th place. One of the biggest factors in English learning is that students need vocabulary mastery. In learning English in elementary school the understanding of English vocabulary is still difficult because teachers deliver learning only by lecture methods, let alone the use of very minimal media, so because of that method teaching and learning process makes the students feel boring because it feels monotonous. One way to make English learning effective is to use a learning model that can provide meaning and fun for students. Team Game Tournament learning model based on Vocabulary Card Media is expected to make students active and excited so that students can easily understand the material studied.